Lipid Accumulation in lipomyces starkeyi cultured in glucose media and sago effluent - AfIzul Safwan, Azahari (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Biodiesel production is a promlsmg alternative for the rapid depletion of non-renewable resources. Utilization of waste residues, agricultural waste and feedstock for production of biodiesel are being implemented due to their potential as replacement for conventional diesel and burning fuels. Oleaginous fungi such as Rhodosporidium sp., Lipomyces sp., and Rhodotorula sp. can be used to hydrolyse these materials and turning them into usable biodiesel. In this project, Lipomyces starkeyi (L. starkeyi) was utilized to compare its performance between two different carbon sources, glucose and sago effluent. Natural sago effluent contain starch, another form of carbon source. Glucose was tested at 2.5% (w/v). Optimum growth ofL. starkeyi was detected at 120 hour. The highest biomass production were recorded at 9.63 giL at 144 h by glucose substrate while only 7.40 giL was produced at 144 h when L. starkeyi utilizes sago effluent. The amount of carbon sources consumed per time were determined by using phenol-sulphuric test. From the lipid extraction stage, glucose substrate can yield about 1.83 giL lipid at 144 h while sago effluent only manages to yield 1.20 giL lipid at 144 h. From this data, L. starkeyi that consumes 2.5% glucose can produce 19.0% of its dry biomass into lipid and when sago effluent was used as the substrate, it can yield 16.2% of its dry biomass. In conclusion, 2.5% glucose is a better substrate in culturing L. starkeyi for lipid production rather than using sago effluent.